Changes to the ownership and control of East Asian corporations between 1996 and 2008: The primacy of politics - Carney, Richard W.; Child, Travers Barclay (Journal of Financial Economics, 2013)
We investigate changes to the ownership and control of East Asia's largest companies in 1996 and 2008. Newly compiled data for 1386 publicly traded companies at the end of 2008 are supplemented with existing data on 1,606 publicly traded companies at the end of 1996. Two main findings stand out. First, where status quo political arrangements persist, preexisting ownership arrangements go unchanged or become more entrenched. Where major political changes occurred, corporate ownership would undergo substantial changes. Second, the state has become increasingly important as an owner of domestic firms as well as foreign firms.